ПРОБЛЕМИ ВИЩОЇ ОСВІТИ НА СУЧАСНОМУ ЕТАПІ РОЗВИТКУ (ЗА МАТЕРІАЛАМИ ПРЕСИ ПІВДНЯ УКРАЇНИ 1991ñ1998 рр.) (Zaporizhzhia Historical Review, 2021)
The contemporary problems of the higher education according to the Southern Ukraine periodicals of 1991-1998 are disclosed. The new trends and changes in the Ukrainian system of higher education are analyzed. The causal factors preventing from the future development of the educational system are shown.